2018
DOI: 10.1186/s40759-018-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of aluminium-graphene composite powders produced by mechanical milling

Abstract: Background: Graphene has been reported to be a promising nanofiller in fabricating advanced metal matrix composites. Methods: Graphene nanosheets (GNSs) have been incorporated into an aluminium matrix composite using mechanical milling and hot pressing in the current study. Results: The SEM observation shows that aluminium particles are firstly flattened into flakes, and then fractured/ rewelded into equiaxed particles as the ball milling progresses. The crystalline size is decreased and the lattice strain is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…10 (a) also show the presence of a detectable amount of the carbides in the SPSed nanocomposites. An increment in the reinforcement addition and higher sintering temperature strongly favours the formation of Al4C3 [55,56]. O for the Al4C3 particles.…”
Section: Resultsmentioning
confidence: 99%
“…10 (a) also show the presence of a detectable amount of the carbides in the SPSed nanocomposites. An increment in the reinforcement addition and higher sintering temperature strongly favours the formation of Al4C3 [55,56]. O for the Al4C3 particles.…”
Section: Resultsmentioning
confidence: 99%
“…Composites of GPL and powdered Al were prepared by Bartolucci et al 99 106 using ball milling technique which depicted high reversible capacity, enhanced cycling stability, and good rate capability to be used as high-performance anode materials for LIBs. Zhang et al 107 prepared GNS-Al nanocomposite using ball milling which revealed increase in hardness by 115.1% due to the refined microstructure and Orowan strengthening.…”
Section: Ball Milling Methodsmentioning
confidence: 99%
“…(d) Deposition of monoatomic carbon coats (graphene) using the CVD method on the surface of Al or Cu wires and their further plastic processing to form wires with required characteristics. (e) Mechanical synthesis of Al powders coated with graphene or Cu powders coated with graphene to a form facilitating their further plastic processing to make wires with required characteristics [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%